The Effectiveness of the Processing Instruction Model - Rodríguez Silva, Luis Humberto; Rodríguez Narciso, Silvia; Eslava Heredia, Cristina; Sanz Martin, Blanca Elena (CIEX JOURNAL, 2024)
The purpose of this study is to verify the efficiency of VanPatten’s (1996) Processing Instruction model in the teaching of English relative clauses in two different groups of participants: an intervention group and a traditional group. These two groups of students were enrolled in a BA in ELT. This study was conducted online due to the pandemic of Covid-19, where a pre-test and a post-test were administered to the intervention group, and only the post-test was administered to the traditional group. The statistical analysis shows a significant difference between the intervention group scores on the pre-test and post-test as well as a significant difference between the traditional group and intervention group. For the qualitative part of the study, the intervention group completed a feedback questionnaire, and the results show that most students consider that employing this model for language teaching is an effective approach in the teaching of relative clauses.